(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
A critical organizational capability in today’s business environment, characterized by a changing and dynamic environment, is change management. Globalization and the exchange of real-time data and information allow organizations to create new business models and concepts, but also lead to the emergence of more competitors that require organizations to increase their potential for innovation in order to maintain competitiveness within the newly created business models. In order to adapt to changes and gain competitive advantage in the market, organizations need to embrace the digital reconstruction of their business model. To incorporate a digital reconstruction strategy, they need to make changes in business models, operating models, human knowledge and skills, and have a high degree of innovation. The advent of digital technology has led to the progressive digitization of processes and functions in organizations during the transition from analogue to digital. It is crucial to make a connection between digital transformation strategies, IT strategies and other organizational and functional strategies. It is important to explore new forms of organizations involved in digital transformation in order to understand how they can be designed and managed effectively.